Profiling Receptor Tyrosine Kinase Fusions in Chinese Breast Cancers - Tao, Zhonghua; Liu, Jianxia; Li, Ting; Xu, Hong; Chen, Kai; Zhang, Jian; Zhou, Hao; Sun, Jie; Han, Jinming; Guo, Zhaoji; Yang, Hua; Cao, Wen-Ming; et al. (Frontiers in Oncology, 2021)
Background: Receptor tyrosine kinases (RTKs) are a class of tyrosine kinases that regulate cell-to-cell communication and control a variety of complex biological functions. Dysregulation of RTK signaling partly due to chromosomal rearrangements leads to novel tyrosine kinase fusion oncoproteins that are possibly driver alterations to cancers. Targeting some RTK fusions with specific tyrosine kinases inhibitors (TKIs) is an effective therapeutic strategy across a spectrum of RTK fusion-related cancers. However, there is still a paucity of extensive RTK fusion investigations in breast cancer. This study aims to characterize RTK fusions in Chinese breast cancer patients. Methods: An in-house DNA sequencing database of 1440 Chinese breast cancer patients with a capture-based panel was thoroughly reviewed. RTK fusion was defined as an in-frame fusion with the tyrosine kinase domain of the RTK completely retained. Concomitant mutations were also analyzed and tumor mutational burden (TMB) was calculated. Results: A total of 30 RTK fusion events were identified from 27 breast cancer patients with a prevalence of 1.9%%. FGFR2 fusions were seen the most commonly (n=7), followed by RET (n=5), ROS1 (n=3), NTRK3 (n=3), BRAF (n=2), and NTRK1 (n=2). Other RTK fusions including ALK, EGFR, FGFR1, FGFR3, MET, and NTRK2 were identified in one patient each. A total of 27 unique resultant fusion proteins (22 with a novel partner) were discovered including 19 intrachromosomal rearrangements and 8 interchromosomal ones. Twenty-one fusions had the tyrosine kinase domain in-frame fused with a partner gene and six were juxtaposed with an intergenic space. Among the 27 fusions, FGFR2-WDR11 (E17: intergenic) (n=3) and ETV6-NTRK3 (E5:E15) (n=2) occurred recurrently. Of note, the normalized abundance of RTK fusion (fusion AF/max AF) correlated negatively with TMB (r=-0.48, P=0.017). Patients with TMB < 8 (Mutations/Mb) displayed a higher fusion abundance than those with TMB ≥ 8 (Mutations/Mb) (P=0.025). Moreover, CREBBP mutation only co-occurred with FGFR2 fusion (P=0.012), while NTRK3 fusion and TP53 mutation were mutually exclusive (P=0.019). Conclusion: This is the first study comprehensively delineating the prevalence and spectrum of RTK fusions in Chinese breast cancers. Further study is ongoing to identify the enriched subpopulation who may benefit from RTK fusion inhibitors.